(3cJGH GdcQI GdeJMQcIs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s; (3GhWhdhbSs
(3ChdgG (B:s
(3GdfbW GdJi jJMQc MQcI eYJOdI Hjf GdJi JSjQ ai CReGf eJSGhjI eJTGHgI s
(3BNQgG (B:s
(3hcGf GdSWM eGFdG gPG Nda bO eQcR GdcQI dGZjQ Je cJGH GdcQI GdeJMQcI s
(3Vef eLehY , JQJjHgG (B: (3GdKGdKs
(3GdfSNI HgG MhGTs
(3GfXQ GdeNWhW Qbe (B66s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(2432/ 3) s
Keywords: (3GdQjGVjGJs